2013
DOI: 10.1073/pnas.1220908110
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the impacts of vaccination and immunity on pertussis epidemiology in Thailand

Abstract: Pertussis is a highly infectious respiratory disease that is currently responsible for nearly 300,000 annual deaths worldwide, primarily in infants in developing countries. Despite sustained high vaccine uptake, a resurgence in pertussis incidence has been reported in a number of countries. This resurgence has led to critical questions regarding the transmission impacts of vaccination and pertussis immunology. We analyzed pertussis incidence in Thailand-both age-stratified and longitudinal aggregate reports-ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 38 publications
3
57
0
Order By: Relevance
“…We did not include this possibility on the basis of the epidemiological data. Some studies have found no empirical evidence in support of the immune boosting hypothesis (17,21), whereas others have found that its epidemiological impact is small, even if statistically significant (52).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We did not include this possibility on the basis of the epidemiological data. Some studies have found no empirical evidence in support of the immune boosting hypothesis (17,21), whereas others have found that its epidemiological impact is small, even if statistically significant (52).…”
Section: Discussionmentioning
confidence: 99%
“…After recovering, individuals are immune to further infection. We assume infection-derived immunity to be lifelong, based on previous epidemiological studies of pertussis in Sweden (22), England and Wales (21), and Thailand (17), which found that repeat infections contributed very little to transmission (57). The number of individuals of each age in each state (susceptible, exposed, infectious, recovered, and vaccinated) is updated stochastically (56).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…IF1 approximates the Fisher score function, whereas IF2 implements an iterated Bayes map. IF1 has been used in applications for which no other computationally feasible algorithm for statistically efficient, likelihoodbased inference was known (10)(11)(12)(13)(14)(15). The extra capabilities offered by IF2 open up further possibilities for drawing inferences about nonlinear partially observed stochastic dynamic models from time series data.…”
Section: Markov Processmentioning
confidence: 99%